Psychological Dynamics of Society about Minimum Age Limit Change for Marriage from the Perspective of Religious Court Judges during the COVID-19 pandemic in Indonesia - Julianto, Very (Journal of Psychological Perspective, 2025)
Underage marriage (UM) has increased globally, including in Indonesia. This was triggered by changes in the Marriage Law (UU) which increased the minimum age for women to marry from 16 to 19 years old and was followed by the emergence of the Covid-19 pandemic. This study examines the psychological dynamics of society related to changes in the minimum age limit for marriage from the perspective of Religious Court judges in Indonesia. A descriptive qualitative approach was used by conducting semi-structured interviews with 20 judges from 16 Religious Courts in Indonesia who handle marriage dispensation cases. This process was followed by data collation, coding, classification, and analysed by the deductive thematic technique. As a result, participants conveyed the background of the age limit change and the public's reaction after the change. Some participants stated that the age limit change is not the authority of the court or judge. Some others said that the increase in the minimum age limit for marriage was carried out based on the risks behind underage marriage. These risks are psychological factors, reducing the number of UM cases, preventing divorce, gender equality, and reasons for education, work, and physical condition. Public showed various responses; obeying the rules, not knowing about the regulatory changes, and being against it. Basically, the new Marriage Law seeks to stop the UM trend. The government needs to conduct socialization about the age limit change and the risks of UM. Cooperation from various parties is also needed, especially from parents who need to pay more attention to their children.